Factors affecting decision making of new graduate physicians in choosing potential areas of practice: A national survey - Ratanachina, Jate; Sathitratanacheewin, Seelwan; Kollawat, Sirawit; Tantitanawat, Kittithat; Pongpirul, Krit (Chulalongkorn Medical Journal, 2023)
Background : In equitable distribution of physicians is a challenge especially in rural areas of developing countries including Thailand. The resignations of newly graduated physicians imply a failure of in comprehensive policy interventions that are not based on real and holistic understanding of the issue. Objective : This study was aimed to empirically explore factors influencing decision making of newly graduated physicians in choosing future practice areas. Design : Descriptive statistics and exploratory factor analysis (EFA) were used for analyzing the responses. Setting : Department of Preventive and Social Medicine, Faculty of Medicine, Chulalongkorn University Methods : A national survey of 751 physicians who graduated from all 12 medical schools in Thailand was conducted in April, 2012. The questionnaire was carefully developed based on literature review and qualitative study that contained three sections: basic information of responding physicians, potential workplace and duration they intended to work, as well as opinions on issues that influence their decision making, using 5-point Likert’s scale. Results : The response rate was 49.93%, almost these 60% were female with average age of 24 years old, compatible with the national profile of Thai physicians. Five factors identified included working condition (daily workload, out-of-hour duty workload and frequency, hospital size), lifestyle quality (environment, food, entertainment, cost of living), essential amenities (e.g. bank), professional development (learning opportunity, staff reputation, familiarity with staff), and adjustment concerns (distance from current residence, parents’ or relatives’ preference, familiarity with the area). Conclusion : At least five factors that influence the decision making of newly graduated physicians in choosing areas of practice were identified. These factors are useful for the development of comprehensive interventions for alleviating inequitable distributions of physicians in developing countries.